2022
DOI: 10.1177/2050313x221113699
|View full text |Cite
|
Sign up to set email alerts
|

A case and literature review of intraocular echinococcus causing bilateral visual loss in a HIV-infected patient

Abstract: Although echinococcosis is a common parasitic disease endemic to Africa, ocular echinococcosis is rare. We present a case of intraocular echinococcosis in a HIV-infected patient. A 38-year-old South African HIV-infected woman presented to a district-level hospital in Kwa-Zulu Natal on 10 March 2020. Her main presenting complaint was that of progressive, painless, bilateral visual loss. A B-ultrasonography scan revealed tractional retinal detachment on the right eye, while the left eye had tractional bands with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Recently, HIV has been reported to be the most frequent immunodeficient infection in patients with CE 2 . In addition, some reports show that extrahepatic cystic disease is more frequent in people with HIV 7 , as has been described in cases with unusual locations such as the brain 13 , spinal cord 14 , eyeball 15 , kidney 16 , kidney-liver 17 ) and peritoneal 18 . Most of these cases occurred in women 2 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, HIV has been reported to be the most frequent immunodeficient infection in patients with CE 2 . In addition, some reports show that extrahepatic cystic disease is more frequent in people with HIV 7 , as has been described in cases with unusual locations such as the brain 13 , spinal cord 14 , eyeball 15 , kidney 16 , kidney-liver 17 ) and peritoneal 18 . Most of these cases occurred in women 2 .…”
Section: Discussionmentioning
confidence: 85%
“…Recientemente, se ha informado que el VIH es la infección inmunodeficiente más frecuente en pacientes con EQ (2) . Además, algunos reportes indican que la enfermedad quística extrahepática es más común en la población con VIH (7) , tal como se ha descrito en casos con localizaciones poco comunes como cerebro (13) , médula espinal (14) , globo ocular (15) , renal (16) , hepatorrenal (17) y peritoneal (18) . La mayor parte de estos casos han ocurrido en mujeres.…”
Section: Discussionunclassified
“…Williams et al reported a choroidal hydatid cyst accompanied by multiorgan involvement in an Alaskan patient [7]. In South Africa, Konar and Pillay reported visual loss in a HIV-infected patient due to bilateral echinococcus cysts and tractional retinal detachment [8]. Guo et al reported a subretinal cyst accompanied by multiple brain lesions in a 37year-old Tibetan patient [9].…”
Section: Discussionmentioning
confidence: 99%